MOA-2010-BLG-328Lb: A sub-Neptune orbiting very late M dwarf? - Furusawa, K.; Udalski, A.; Sumi, T.; Bennett, D.; Bond, I.; Gould, A.; Jørgensen, U.; Snodgrass, C.; Dominis Prester, D.; Albrow, M.; Abe, F.; Botzler, C.; et al. (IOP Publishing Ltd., 2013)
We analyze the planetary microlensing event MOA-2010-BLG-328. The best fit yields host and planetary massesof Mh = 0.11 ± 0.01M and Mp = 9.2 ± 2.2M?, corresponding to a very late M dwarf and sub-Neptune-massplanet, respectively. The system lies at DL = 0.81 ± 0.10 kpc with projected separation r? = 0.92 ± 0.16 AU.Because of the host’s a priori unlikely close distance, as well as the unusual nature of the system, we considerthe possibility that the microlens parallax signal, which determines the host mass and distance, is actually due toxallarap (source orbital motion) that is being misinterpreted as parallax. We show a result that favors the parallaxsolution, even given its close host distance. We show that future high-resolution astrometric measurements coulddecisively resolve the remaining ambiguity of these solutions.